A vida em semiliberdade: um estudo sobre adolescentes em conflito com a lei - Pereira, Almunita dos Santos Ferreira (2007)
In the first part, the present study had as a goal to tell the experiences and emotions I lived when I was an employee of Febem/SP. Having this institution as background to place the research. These experiences and emotions reveal the everyday life of the adolescents in conflict with the law in fullfilment of socioeducational measures. By telling all this, I tried to overcome the walls and gates of Febem, showing a world not well-known to outsiders. In the second part, the research was dedicated to the study of the everyday life of adolescent in conflict with the law in fullfilment of semi liberty socioeducational measure of internment. This discussion aimed at, by analyzing the adolescent s speech, understanding his experiences and emotions and investigating how the adolescent deals with the measure. This is a qualitative research and it was done in a Febem institution. Three adolescents took part of it. They aged from 16 to 17 and were in conflict with the law in fulfillment of socioeducational measure. The individual interview was the main instrument to collect data. The data analysis have showed that, in spite of the fact that the socioeducational measure allows the adolescents to go out and to visit the family on the weekends, the adolescents keep on living moments of anguish and stress due to the norms and imposed rules. Despite the difficulties, they say that the effective norms are necessary for their re-socialization; besides, they show, during interview, ambiguities and contradictions in relation to their future choices. The consumption culture emerges as the main reason of the juvenile delinquency. They perceive the rules of the measure as a penalty that restrict the freedom and the satisfaction of their desires, and the vulnerability is the source to make them break the law. For the interviewed adolescents the challenge is the future, which is linked to the satisfaction of desires of consumption. However, satisfying these desires is almost impossible for these adolescents due to their social economic status